1994
DOI: 10.2109/jcersj.102.742
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior and Microstructure of Hydrothermally Treated Monodispersed Titanium Dioxide Particles

Abstract: Spherical amorphous monodispersed titanium dioxide particles were synthesized by hydrolysis of titaniumtetra-ethoxide (Ti(OC2H5)4) in dilute ethanol solution and were hydrothermally treated using an autoclave. The amorphous monodispersed titanium dioxide parti cle were crystallized and many nano-sized particles of anatase single crystal produced in the particle by the hydrothermal treatment. The internal microstructure of the hydrothermally treated monodispersed titanium dioxide particle was homogeneous. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…2 and Table 1). The behavior of T/GS-10 may be explained as formation and growth of rutile crystals during hydrothermal aging (in acidic medium), which proceeded at the expenses of anatase crystals, possibly via a dissolution-precipitation mechanism [37] or by condensation of the anatase nanoparticles where, during the growth of small anatase particles by ripening, a join of their (112) facets is produced. However, this explanation does not account for the different behavior observed in the rest of samples of this series (T/GS-5, and T/GS-20) and, to this moment, we do not have a clear explanation for this feature.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…2 and Table 1). The behavior of T/GS-10 may be explained as formation and growth of rutile crystals during hydrothermal aging (in acidic medium), which proceeded at the expenses of anatase crystals, possibly via a dissolution-precipitation mechanism [37] or by condensation of the anatase nanoparticles where, during the growth of small anatase particles by ripening, a join of their (112) facets is produced. However, this explanation does not account for the different behavior observed in the rest of samples of this series (T/GS-5, and T/GS-20) and, to this moment, we do not have a clear explanation for this feature.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…4 Other researchers have studied the influence of water content, time, and temperature on hydrothermal crystallization of anatase from hydrous titania. 5,6 Revathi et al investigated the hydrothermal crystallization of unpeptized and peptized titania sols and found that hydrothermal processing of unpeptized titania precipitated from alkoxide showed highly crystallized anatase powder in all cases. However, when the precursor was peptized, i.e., precipitates were redispersed in nitric acid and refluxed to obtain transparent sols, a very small amount of rutile powder was obtained together with anatase powders from ethoxide and isopropoxide whereas the powders from tert-butoxide contained only anatase phase.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 -NP have potential remarkable applications as an attractive filler for multifunctional materials, due to their unique properties such as higher stability, long lasting, safe and broad-spectrum antibiosis (Roessler et al 2002;Cai et al 2006). Common preparation of these types of bionanocomposites included hydrolysis of the metal compounds and dehydration (Montoya et al 1992), sol-gel (Barringer and Bowen 1982), a hydrothermal method (Kondo et al 1994), or modification of commercially available TiO 2 . Common preparation of these types of bionanocomposites included hydrolysis of the metal compounds and dehydration (Montoya et al 1992), sol-gel (Barringer and Bowen 1982), a hydrothermal method (Kondo et al 1994), or modification of commercially available TiO 2 .…”
Section: Nanocomposites: Starch/antioxidants And/ or Antimicrobialsmentioning
confidence: 99%